LAJU DAN KONDISI SEDIMENTASI PADA EKOSISTEM TERUMBU KARANG DI PULAU BALLANG LOMPO KABUPATEN PANGKEP, PROVINSI SULAWESI SELATAN - Mutmainnah, Mutmainnah; Adrianto, Luky; Kusumastanto, Tridoyo; Yulianda, Fredinan (FAPETKAN UNTAD, 2011)
The research was located at Balang Lompo Island Mattiro Sompe District Pangkep Regency, South Sulawesi from July to December 2009. The aim of this research was to measure sedimentation rate and to analyze sediment type that precipitates on Terumbu’s ecosystem at Ballanglompo Island. The results of analysis indicated sedimentation rate in the waters of Ballanglompo Island was about 0.0036 – 0.300 mg/cm2/day. This sedimentation rate was still very low with sediment size of 0.5 – 0.125 mm which is classified as sand. Key words : Balang Lompo Island, coral reef, sedimentation.